Nuclear localisation sequences of chloride intracellular channels 1 and 4 facilitate nuclear import via interactions with import mediator importin‐α: An empirical and theoretical perspective. Issue 2 (10th December 2022) - Færch, Olga; Worth, Roland; Achilonu, Ikechukwu; Dirr, Heini
Abstract: Chloride intracellular channel proteins (CLICs) display ubiquitous expression, with each member exhibiting specific subcellular localisation. While all CLICs, except CLIC3, exhibit a highly conserved putative nuclear localisation sequence (NLS), only CLIC1, CLIC3 and CLIC4 exist within the nucleus. The CLIC4 NLS, 199‐KVVAKKYR ‐206, appears crucial for nuclear entry and interacts with mouse nuclear import mediator Impα isoform 1, omitting the IBB domain (mImpα1ΔIBB). The essential nature of the basic residues in the CLIC4 NLS has been established by the fact that mutating out these residues inhibits nuclear import, which in turn is linked to cutaneous squamous cell cancer. Given the conservation of the CLIC NLS, CLIC1 likely follows a similar import pathway to CLIC4. Peptides of the CLIC1 (Pep1; Pep1_S C/S mutant) and CLIC4 (Pep4) NLSs were designed to examine binding to human Impα isoform 1, omitting the IBB domain (hImpα1ΔIBB). Molecular docking indicated that the core CLIC NLS region (KKYR ) forms a similar binding pattern to both mImpα1ΔIBB and hImpα1ΔIBB. Fluorescence quenching demonstrated that Pep1_S ( K d  ≈ 237 μM) and Pep4 ( K d  ≈ 317 μM) bind hImpα1ΔIBB weakly. Isothermal titration calorimetry confirmed the weak binding interaction between Pep4 and hImpα1ΔIBB ( K d  ≈ 130 μM) and the presence of a proton‐linked effect. This weak interaction may be due to regions distal from the CLIC NLS needed to stabilise and strengthen hImpα1ΔIBB binding. Additionally, this NLS may preferentially bind another hImpα isoform with different flexibility properties. Abstract : Structural and CLIC unclear localisation sequence binding differences between mouse Importin α1 (grey) and human Importin α1 (green) show conformational and sequence differences between the two structures. Nonetheless, the major binding pocket of Impα for interacting with cargo NLSs is highly conserved.